2016
DOI: 10.1371/journal.pone.0159293
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Quality of Life in Ageing Populations: Results from a Cross-Sectional Study in Finland, Poland and Spain

Abstract: PurposeTo comprehensively identify the determinants of quality of life (QoL) in a population study sample of persons aged 18–50 and 50+.MethodsIn this observational, cross-sectional study, QoL was measured with the WHOQOL-AGE, a brief instrument designed to measure QoL in older adults. Eight hierarchical regression models were performed to identify determinants of QoL. Variables were entered in the following order: Sociodemographic; Health Habits; Chronic Conditions; Health State description; Vision and Hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 61 publications
7
73
1
4
Order By: Relevance
“…Raggi et al proved that in Poland older age has particularly significant impact on lowering the QOL, while, e.g. in Spain the significant factors resulting in a lowered QOL were depression and alcohol consumption, and in Finland -ischaemic heart disease [18]. The relationship between individual QOL and age seems controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raggi et al proved that in Poland older age has particularly significant impact on lowering the QOL, while, e.g. in Spain the significant factors resulting in a lowered QOL were depression and alcohol consumption, and in Finland -ischaemic heart disease [18]. The relationship between individual QOL and age seems controversial.…”
Section: Discussionmentioning
confidence: 99%
“…This is related to a low level of adaptation of an elderly body [23]. Other studies stressed the burden of heath related problems and pain on lowered quality of life of older adults [18]. Analysis of regression by Kumar et al showed a significant impact of musculoskeletal disorders (p ≤ 0.001), poor eyesight (p = 0.049) and hearing impairment (p = 0.001) on QOL [17].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were performed without adjustments (crude model), adjusted for age, sex, and study center (Model 1), and additional adjustments for education level, smoking behavior, alcohol consumption, creatinine concentrations, BMI, and MMSE (Model 2). These covariates were added because of their possible influence on both the determinant (Hcy) and the outcomes (depressive symptoms, HR-QoL) [2,41,42]. …”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study carried out in Finland, Poland, and Spain evaluated the determinants of the quality of life of elderly people, and showed that the practice of physical activity and the establishment of bonds through the insertion of elderly people into social groups are some of the factors that contribute to the increase in quality of life of the aging population (10) . A study carried out in Brazil showed that the elderly did not isolate themselves at home; they sought active insertion into groups in the community, establishing new bonds and friendships (11) .…”
Section: Discussionmentioning
confidence: 99%